Virtual Reality Animal Rescue World: Pediatric virtual reality analgesia during just noticeable pressure pain in children aged 2–10 years old (crossover design) - Alrimy, Taima; Alhalabi, Wadee; Malibari, Areej A.; Alzahrani, Fatma Salih; Alrajhi, Sharifah; Alhalabi, Mohammed; Hoffman, Hunter G. (Frontiers in psychology, 2022)
Excessive pain during medical procedures is a worldwide medical problem. Most scald burns occur in children under 6, who are often undermedicated. Adjunctive Virtual Reality (VR) distraction has been shown to reduce pain in children aged 6-17, but little is known about VR analgesia in young children. This study tests whether desktop VR (VR Animal Rescue World) can reduce the just noticeable pressure pain of children aged 2-10.Background and aimsExcessive pain during medical procedures is a worldwide medical problem. Most scald burns occur in children under 6, who are often undermedicated. Adjunctive Virtual Reality (VR) distraction has been shown to reduce pain in children aged 6-17, but little is known about VR analgesia in young children. This study tests whether desktop VR (VR Animal Rescue World) can reduce the just noticeable pressure pain of children aged 2-10.A within-subject repeated measures design was used. With treatment order randomized, each healthy volunteer pediatric participant underwent brief cutaneous pressure stimuli under three conditions: (1) no distraction, (2) a verbal color naming task (no VR), and (3) a large TV-based desktop VR distraction. A hand-held Wagner pressure pain stimulation device was used to generate just noticeable pain sensations. Participants indicated when a steadily increasing non-painful pressure stimulus first turned into a painful pressure sensation (just noticeable pain).MethodsA within-subject repeated measures design was used. With treatment order randomized, each healthy volunteer pediatric participant underwent brief cutaneous pressure stimuli under three conditions: (1) no distraction, (2) a verbal color naming task (no VR), and (3) a large TV-based desktop VR distraction. A hand-held Wagner pressure pain stimulation device was used to generate just noticeable pain sensations. Participants indicated when a steadily increasing non-painful pressure stimulus first turned into a painful pressure sensation (just noticeable pain).A total of 40 healthy children participated (43% aged 2-5 years; and 57% aged 6-10 years). Compared to the no distraction condition, the 40 children showed significant VR analgesia (i.e., a significant reduction in pain sensitivity during the VR Animal Rescue World condition), t(39) = 9.83, p < 0.001, SD = 6.24. VR was also significantly more effective at reducing pain sensitivity vs. an auditory color naming task, t(39) = 5.42, p < 0.001, SD = 5.94. The subset of children aged 2-5 showed significant reductions in pain during VR. Children under 6 showed greater sensitivity to pain during no distraction than children aged 6-10.ResultsA total of 40 healthy children participated (43% aged 2-5 years; and 57% aged 6-10 years). Compared to the no distraction condition, the 40 children showed significant VR analgesia (i.e., a significant reduction in pain sensitivity during the VR Animal Rescue World condition), t(39) = 9.83, p < 0.001, SD = 6.24. VR was also significantly more effective at reducing pain sensitivity vs. an auditory color naming task, t(39) = 5.42, p < 0.001, SD = 5.94. The subset of children aged 2-5 showed significant reductions in pain during VR. Children under 6 showed greater sensitivity to pain during no distraction than children aged 6-10.During no distraction, children under 6 years old were significantly more sensitive to pain than children aged 6-10. Virtual reality (VR) significantly reduced the "just noticeable" pressure pain sensitivity of children in both age groups.ConclusionDuring no distraction, children under 6 years old were significantly more sensitive to pain than children aged 6-10. Virtual reality (VR) significantly reduced the "just noticeable" pressure pain sensitivity of children in both age groups.